Between the lines : South Asians and postcoloniality - Bahri, Deepika, 1962-; Vasudeva, Mary, 1966- (Asian American history and culture., 1996)
This collection of interviews, critical essays, and commentary explores South Asian identity and culture in the United States and Canada and attempts to explore the differences among the false homogeneity implied by the term "Asian American."